MIGRASI INTERNASIONAL PEREMPUAN DAN PENGUASAAN LAHAN PEDESAAN DI JAWA BARAT - Ekawati Sri Wahyuni; Lala M. Kolopaking; Endriatmo Soetarto (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2012)
This paper is a result of a research on women in Panyingkiran Village (Karawang) and Ciherang Village (Purwakarta) of West Java-Indonesia who migrate internationally. Paradigm used in this research is Post-Positivism which integrates quantitative and qualitative methods. Primary data is collected through in depth interview and Focus Group Discussion. The result of the research shows that most of female migrants spend remittent from working in Saudi to buy land (dry land and paddy rice fields) of relatively small in size. Land is an interesting choice because: (1) female migrants come from poor families which are the lowest class in rural areas; (2) the livelihood of female migrants’ families are farm labors and landless farmers; (3) occupations of migrants before going abroad are farm labors, jobless and as house wife; (4) farm land is a social status symbol for rural communities; (5) land is a saving and land ownership is also a capital when one dies, and becomes a standard in the ritual of death ngamumule or mulasara.